Effects of summer supplementation of Houttuynia cordata extract on growth performance, anti-inflammatory properties, and rumen fermentation in Guizhou black goats - Xie, Lingling; Jian, Zhongling; Tang, Mingyan; Li, Chen; Huang, Zhiyu; Wang, Fu; Ou, Ren; Lu, Shengyong (Frontiers in Veterinary Science, 2025)
The aim of this study was to examine the effects of supplementing Guizhou black goats with Houttuynia cordata extract (HCE) during summer on growth performance, anti-inflammatory activity, and rumen fermentation parameters. A completely randomized single-factor experimental design was employed. Twenty-four healthy Guizhou black goats, with similar body weights (16.03 ± 0.79 kg), were randomly divided into three groups, with eight replicates per group and one goat per replicate. The control group (CON) was fed a basal diet, the LC and HC groups received the basal diet supplemented with 500 mg/kg and 1,000 mg/kg of HCE, respectively. The ADG in the HC group was significantly higher (p < 0.05) than that in the CON group. The digestibility of DM in both the LC and HC groups was significantly higher (p < 0.05) than in the CON group. Additionally, the digestibility of CP, GE, and NDF in the HC group was significantly higher (p < 0.05) than in the CON group. GSH-Px levels in both the LC and HC groups were significantly higher (p < 0.05) than in the CON group. T-AOC in the HC group was also significantly higher (p < 0.05) than in the CON group. MDA levels in the HC group were significantly lower (p < 0.05) than in both the LC and CON groups (p < 0.05). The TP content in the HC group was significantly higher (p < 0.05) than in the CON group. IgA levels in both the LC and HC groups were significantly higher (p < 0.05) than in the CON group. The levels of IL-6 and IL-8 in the HC group were significantly lower (p < 0.05) than in the LC and CON groups. Interestingly, the IL-10 level in the HC group was significantly higher (p < 0.05) than in the LC and CON groups. The TNF-α level in the HC group was significantly lower (p < 0.05) than in the CON group. The HCE had no significant (p > 0.05) effect on rumen pH, NH3-N, and VFAs. In conclusion, a high dose of HCE improved growth performance, apparent nutrient digestibility, and enhanced antioxidant, immune, and anti-inflammatory responses in goats.